Role of CXCR4 and MMP-9 Expressions with Regional Cervical Lymph Nodes Metastatic Status in Papillary Thyroid Carcinoma - Etty Hary Kusumastuti; Nurdhani Hi Djafar; Alphania Rahniayu (Indonesian Journal of Cancer, 2021)
Background: Papillary thyroid carcinoma (PTC) that has metastasized has a higher risk because of the poor prognosis, ranging from decreased quality of life of the patient to death. There is a need for markers that can understand the image of the tumor so that it can predict earlier the level of aggressiveness and the ability of tumor cells to metastasize. Tumor cells that proliferate excessively will cause CXCR4 expression. Activation of CXCR4 will increase MMP-9 via the MAPK/ ERK line. MMP-9 will degrade the extracellular matrix causing tumor cell metastasis. This study is aimed to analyze the correlation of CXCR4 and MMP-9 expressions with lymph node metastasis (LNM) in PTC.Methods: This cross-sectional analytic observational study was conducted in 43 PTC samples taken from the Anatomical Pathology Laboratory of Dr. Soetomo Hospital from January 2011 to December 2018. The samples were divided into 2 groups based on the regional cervical LNM status. Immunohistochemical staining was used to assess the expression of CXCR4 and MMP-9. Spearman test was used to analyze the correlation of CXCR4 and MMP expression with cervical LNM status.Results: The expression of CXCR4 and MMP-9 was higher in the papillary thyroid carcinoma group with cervical regional LNM (p = 0.007 and p = 0.030). There was a significant positive relationship between CXCR4 and MMP-9 expressions with regional LNM status with rs = 0.468 and p = 0.001 (p < 0.05). Conclusions: Expression of CXCR4 and MMP-9 was proven to correlate with regional cervical LNM status in papillary thyroid carcinoma. Both can be used as predictive markers for metastasis in papillary thyroid carcinoma.